Theoretical Rationale for the Combined Use of Gabapentin and Fingolimod for the Treatment of Multiple Sclerosis Using in silico Methods - Larionov, V.; Nefedov, O.; Belenichev, I. F.; Kalbus, O.; Nefedova, O.; Sаmura, I. B.; Bukhtiyarova, N. V.; Бєленічев, Ігор Федорович; Самура, Ірина Борисівна; Бухтіярова, Ніна Вікторівна (My University, 2024)
Chronic neuropathic pain in multiple sclerosis is found in 25-90 % of patients. Optimal pharmacotherapy should include both diseasemodifying agents and medications that affect neuropathic pain. Taking into account that the development of multiple sclerosis is based on a chronic demyelinating inflammatory process (foci of demyelination), the rational treatment of relapsing-remitting multiple sclerosis should include both disease-modifying therapy and symptomatic therapy, in particular, medications affecting neuropathic pain. The study showed that under physiological conditions, ionic interaction between fingolimod and gabapentin is possible with the formation of salts capable of reversible dissociation without changing the molecule’s structure, and with the formation of the corresponding protonated forms. The acid-base properties of the compounds were analyzed using the ACD/pKaDB and ChemAxon programs. At the pharmacokinetic level, no interaction is expected between finngolimod and gabapentin as they use different transport systems, and different metabolic enzymes. Fingolimod and gabapentin differ significantly in the extent of plasma proteins binding, which excludes their interaction during absorption, distribution, metabolism, and excretion. Therefore, the synergistic combination of fingolimod and gabapentin can be a promising therapeutic alternative for the effective treatment of multiple sclerosis. Its positive additive effects are expected to relieve symptoms of the disease, reduce the intensity of inflammatory processes in the central nervous system, produce a neuroprotective effect, contribute to remyelination due to the action of fingolimod, and relieve symptoms of neuropathic pain under the influence of gabapentin.
Keywords: Multiple sclerosis; combination therapy; fingolimod; gabapentin